Proyecto de factibilidad para la producción y comercialización de café molido en la ciudad de Portovelo Provincia de El Oro - Ortiz Ordoñez, Manuel Patricio (2018)
Many economic sectors of our country agree that the support to the microenterprise is the way to reactivate production in Ecuador, however, there are several limitations for this sector to reach a continuous growth, for this reason is that it seeks to promote the entrepreneurship or innovate business ideas generating sources of employment and contributing to the economy of the country. For this reason it has been considered convenient to carry out a "PROJECT OF FEASIBILITY FOR PRODUCTION AND COMMERCIALIZATION OF GROUND COFFEE IN THE CITY OF PORTOVELO PROVINCE OF EL ORO" The general objective is to carry out a feasibility study to determine the possibility of creating a company to produce and sell ground coffee in the city of Portovelo. Likewise, the specific objectives that are pursued are: to carry out a market study to determine the supply and demand of the product; determine the functional and manual organic structure of legal functions; conduct a technical study to determine the size and location of the company, project engineering and organizational design; conduct a financial study and financial evaluation to determine investments and their financing; all this in order to determine the viability of the project. 6 The methods and techniques used in the development of this work were: Deductive, Inductive, Analytical and Statistical, while in the techniques the survey and direct observation were used. For the segmentation of the market, the population of the city of Portovelo was taken in 2010; according to the National Institute of Statistics and Census (INEC) were 9,996 inhabitants likewise a projection according to the growth rate of 1.52% for the year 2017 resulting 11,109.32 inhabitants per family later diversify resulting performed a sample of 2,777.33 families with whom we proceeded to work. For the implementation of the present feasibility study, an analysis was conducted where it was possible to know the reception and profitability that this product will have in the city of Portovelo. To do this, the following studies were considered: In the market study, the supply and demand of this product within the market was analyzed, obtaining an effective demand of 41,120 pounds of coffee in the first year; and an unsatisfied demand of 2,202 pounds of coffee the first year; likewise, the marketing plan will be carried out in Producer - Distributor - Final Consumer form. In the technical study is analyzed machinery, equipment, labor, which will be used for the manufacture of ground coffee, also know the production processes, as well as the installed capacity that is 72,800 pounds per year, while the capacity used It is 72,800 pounds annually. 7 Legal Administrative Study, it was established that the company will be constituted as a one-person organization with limited liability. In the Financial Study, the initial investment of the project is determined, this being of $ 30,095.77; will be incurred in a financing from a local financial institution such as "BanEcuador", this entity will finance 33.23% of the total value of the investment. It also presents indicators such as the Net Present Value (NPV) which yields a positive result of $ 26,956.35, the Cost Benefit Ratio (RBC) is $ 0.09ctvs. profit for every dollar invested in the internal rate of return of 40.47% a percentage that is greater than the opportunity cost of capital was obtained while the Recovery Period Capital said the investment will recover in the period of 2 years 0 months 27 days, according to the Sensitivity Analysis, it was obtained that with an increase in costs of 7.43% a sensitivity value of 0.99 was obtained and a decrease in income of 6.46% was obtained. a sensitivity value of 0.99. Once the various studies were completed, the respective conclusions and recommendations were made.